Hành vi công dân tổ chức của giảng viên đại học ở Việt Nam: Vai trò của phong cách lãnh đạo chuyển dạng, cam kết về khía cạnh cảm xúc và sự vượt qua cái tôi - Lê Nhật , Hạnh; Hồ Xuân , Hướng; Nguyễn Ngọc , Đức (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
Organizational citizenship behavior of faculty members refers to voluntary behaviors that go beyond the requirements of duties and responsibilities of the assigned work, which is a key factor to motivate faculty members to fulfill their roles as educators, researchers and educational service providers to the community. The purpose of this study is to test the impacts of transformational leadership, affective commitment, and self-transcendence on the organizational citizenship behavior of faculty members. The data was collected from a survey of 333 lecturers working at several Vietnamese universities. Partial Least Square - Structural Equation Model (PLS-SEM) was used to test the research model and hypotheses. Research results show that transformational leadership has a strong positive influence on organizational citizenship through promoting affective commitment and nurturing transcendent values beyond the self. The study has important academic and management implications for educational leaders and practitioners.